Functional diversity and ecological niches of C4 climate-resilient species to guide island ecosystem restoration - Rocha, Vanézia; Romeiras, Maria Manuel; Vasconcelos, Maria José; Duarte, Maria Cristina (Frontiers in Environmental Science, 2025)
IntroductionArid ecosystems impose particularly harsh conditions on plants. To thrive, many species have evolved a range of adaptive traits, among which those with C4 photosynthesis are recognised for their high efficiency in hot and dry environments. Therefore, these species are considered crucial for the restoration and management of dry tropical ecosystems. However, their ecological and functional roles remain poorly understood on oceanic islands such as Cabo Verde.MethodsThis study, based on herbarium records, GBIF occurrences, and validated field data, presents an analysis of the functional diversity of 162 C4 species (4,846 occurrences) recorded in the Cabo Verde Islands, representing about 21.6% of the vascular flora of the archipelago. The species were characterised by their functional traits (including life cycle, habit, salinity tolerance, and photosynthetic subtypes NADP-ME, NAD-ME, and PEP-CK), altitudinal distribution, and climatic preferences for temperature and precipitation.ResultsThe results reveal marked differences in ecological distribution between C4 eudicots and monocots: eudicots are more frequent in arid and saline habitats at low elevations, whereas monocots occupy a wider ecological range. C4 halophytes, in particular, show promise for nature-based solutions such as coastal revegetation and soil restoration in degraded areas. The analysis highlights species with strong potential for revegetation and ecosystem management, especially in insular contexts exposed to water scarcity and climate stress. Salinity-adapted annuals and perennials are especially relevant, along with C4 lineages linked to photosynthetic subtypes that confer enhanced environmental resilience.DiscussionThis functional and ecological assessment provides a scientific basis for selecting climate-resilient species to support revegetation and sustainable management of fragile dry tropical island ecosystems. Indeed, understanding the functional differences between C4 monocots and C4 eudicots is essential for developing climate-smart revegetation strategies. The approach adopted here promotes the conservation of biodiversity through functional perspectives, offering a model of ecological action in vulnerable regions under climate change. The findings underscore the ecological preferences of the C4 species and highlight their potential contributions to ecosystem function, resilience, and restoration.